2011
DOI: 10.1002/rcm.5260
|View full text |Cite
|
Sign up to set email alerts
|

Formation of tungstate‐containing cluster ions by polyoxotungstate anions under matrix‐assisted laser desorption/ionization conditions in the gas phase

Abstract: The gas-phase studies of transition-metal oxides continue to attract interest as such oxides are being used as catalysts in various oxidation processes. In this paper, singly negatively charged heteropolyoxotungstate and isopolyoxotungstate ion clusters were produced from Keggin-type polyoxotungstates by matrix-assisted laser desorption/ionization Fourier transform ion cyclotron resonance mass spectrometry (MALDI-FTICR MS). It was found that the ion series [(PO(3))(WO(3))(n)](-), [(WO(3))(n)](-) and [(OH)(WO(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In each ion series, the most abundant ions (magic numbers) were the [(HSiO 3 )(WO 3 ) 6 ] − , [(C 8 H 5 O m )(WO 3 ) 3 ] − , [(HO)(WO 3 ) 6 ] − , and [(W 7 O 21 ] −• cluster ions, respectively, which indicates their relatively more stable structures. We have previously reported that the DIT matrix can interact with tungstate anions to form an organic–inorganic hybrid [W 2 C 14 H 7 O 8 ] − ion cluster 19,20 . Likewise, it seems that the matrices DHAP and THAP can also interact with tungstate anions to generate a series of organic–inorganic hybrid tungsten‐containing ion clusters [(C 8 H 5 O m )(WO 3 ) n (H 2 O) x ] − in the gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…In each ion series, the most abundant ions (magic numbers) were the [(HSiO 3 )(WO 3 ) 6 ] − , [(C 8 H 5 O m )(WO 3 ) 3 ] − , [(HO)(WO 3 ) 6 ] − , and [(W 7 O 21 ] −• cluster ions, respectively, which indicates their relatively more stable structures. We have previously reported that the DIT matrix can interact with tungstate anions to form an organic–inorganic hybrid [W 2 C 14 H 7 O 8 ] − ion cluster 19,20 . Likewise, it seems that the matrices DHAP and THAP can also interact with tungstate anions to generate a series of organic–inorganic hybrid tungsten‐containing ion clusters [(C 8 H 5 O m )(WO 3 ) n (H 2 O) x ] − in the gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a–b shows negative ion SALDI mass spectra of dodecatungstosilicic acid (H 4 SiW 12 O 40 , SiW12) and phosphomolybdic acid (H 3 PMo 12 O 40 , PMo12), which are typical POMs, obtained by using TNC substrates. By careful and detailed study, the SALDI‐MS signals were assigned as shown in Tables S1–2 …”
Section: Resultsmentioning
confidence: 99%
“…1, members . Unlike phospho-polyoxotungstate ion clusters [4] , molybdenum-tooxygen ratios are not in accordance with certain laws in phospho-polyoxomolybdate ion clusters when the numbers of molybdenum atoms are more than 6, such as [PMo 7 O 22 ] -, [PMo 14 O 42 ] -.…”
Section: Dear Sirmentioning
confidence: 98%
“…[1] Matrix-assisted laser desorption/ionization (MALDI) is an important mass spectrometric technique, [2] which has some inherent advantages, such as relatively low sample requirements, sensitivity and straightforward mixture analysis. Sometimes, some series of metal-related ion clusters can be efficiently produced by MALDI source [3][4][5] since the physical aspects of MALDI overlap with the laser ablation (LA) of molecular substrates to some extent [6] , particularly with the advent of delayed ion extraction and novel surface preparation protocolsdirectly dropping analytes from the solution on top of the pre-deposited matrix layer. In LA, two mechanisms could explain the formation of ionic species: [7] recombination and unimolecular dissociation before detection.…”
mentioning
confidence: 99%